Cardiac pacing in children. Issue 7 (July 1982) - Ward, D E; Signy, M; Oldershaw, P; Jones, S; Shinebourne, E A
Abstract : Twenty patients aged between 12 months and 13 years underwent permanent pacemaker implantation. The main indication for pacing was post-surgical atrioventricular block. The complication rate was high and related mainly to infections and lead system problems. The use of small multiprogrammable pacemakers is expected to reduce the reoperation rate for system malfunction and elective replacement. Newer methods of electrode insertion and active fixation devices in smaller diameter leads make endocardial pacing a practical alternative to epicardial pacing in the larger child who did not require a pacing system at the time of surgery.